2006
DOI: 10.1007/s00267-004-0371-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Use of Indigenous Knowledge with Classification and Ordination Techniques for Assessing the Species Composition and Structure of Vegetation in a Tropical Forest

Abstract: Identification of groups that are similar in their floristic composition and structure (habitat types) is essential for conservation and forest managers to allocate high priority areas and to designate areas for reserves, refuges, and other protected areas. In this study, the use of indigenous knowledge for the identification of habitat types in the field was compared against an ecological characterization of habitat types, including their species composition obtained by using classification and ordination tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Stand age was determined from interviews with local residents who lived in the area for at least 40 years and owned or worked on the land. Mayan farmers have a keen empirical knowledge of forest succession, and their own detailed system of classifying and distinguishing several successional stages based on their knowledge of the local disturbance regime, and the presence and size of certain species, which makes their determination of forest stand age reliable [43]. In total, there were 276 plots consisting of two concentric circular areas, one of 200 m 2 where all tress with a diameter at breast height (DBH; 1.3 m height) >5 cm were measured, and the other one of 50 m 2 where all plants of tree I.V. "…”
Section: Species Selectionmentioning
confidence: 99%
“…Stand age was determined from interviews with local residents who lived in the area for at least 40 years and owned or worked on the land. Mayan farmers have a keen empirical knowledge of forest succession, and their own detailed system of classifying and distinguishing several successional stages based on their knowledge of the local disturbance regime, and the presence and size of certain species, which makes their determination of forest stand age reliable [43]. In total, there were 276 plots consisting of two concentric circular areas, one of 200 m 2 where all tress with a diameter at breast height (DBH; 1.3 m height) >5 cm were measured, and the other one of 50 m 2 where all plants of tree I.V. "…”
Section: Species Selectionmentioning
confidence: 99%
“…Despite the importance of LEK to conservation management (Huntington 2000, Brook and McLachlan 2008, Anadón et al 2009, its accuracy is rarely tested (Davis and Ruddle 2010). The few studies to test the accuracy of LEK held by traditional owners and farmers relative to empirical scientific data have concluded that it can provide an important source of evidence (Aswani and Hamilton 2004, Aswani and Lauer 2006, Hernandez-Stefanoni et al 2006, Lauer and Aswani 2008, Anadón et al 2009) but can also have limitations Hamilton 2004, Gilchrist et al 2005). Although the knowledge of practitioners is widely used and has the potential to significantly influence management outcomes, we know of no studies to test the accuracy of practitioners' judgments about the conditions in their reserves.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that indigenous cultures living in tropical forests use meticulous classification systems to distinguish between vegetation types on the landscape (Abraã o et al 2008;Fleck and Harder 2000;Gilmore and Young 2010;Hernandez-Stefanoni et al 2006;Shepard et al 2001;Torre-Cuadros and Ross 2003). For example, Shepard et al (2004) reported that the Matsigenka of southeastern Peru distinguish at least 61 different vegetation types in the lowlands of Manu National Park.…”
Section: Introductionmentioning
confidence: 99%